Correction: Preparation of fluorescent graphene quantum dots from humic acid for bioimaging application. (9th September 2022) - Shi, Weijie; Fan, Hai; Ai, Shiyun; Zhu, Lusheng
Abstract : Correction for 'Preparation of fluorescent graphene quantum dots from humic acid for bioimaging application' by Weijie Shi et al., New J. Chem., 2015, 39, 7054–7059, ; https://doi.org/10.1039/C5NJ00760G .